KEPUTUSAN PEMBELIAN PADA UMKM PRODUK LOKAL GARUT DIPENGARUHI OLEH VARIASI PRODUK - hari mulia (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
Purchasing decision is the decision-making stage where consumers actually buy a product or service. This research is motivated by the decline in sales of Dodol products as a local product typical of Garut at one of the SMEs selling dodol in the last five years, from 2013-1017. This indicates that Dodol consumers are starting to switch to other products. The purpose of this study was to determine whether product variations affect purchasing decisions. The population in this research are Dodol Bestory consumers, while the sample taken is 68 respondents using a non-probability technique with an incidental sampling approach. Based on the analysis and data obtained using SPSS Version 16, that the description of the research instrument used in this study is declared valid and reliable, because it has a value greater than r table. From the results of the correlation test that product variations have an influence on purchasing decisions with a correlation value (r) of 0.550, a coefficient of determination of 30.2% and a significant test value of 5.537. Thus it can be concluded that product variations have a positive and significant influence on consumer purchasing decisions. If product variety is increased, consumer decisions will also increase